1998
DOI: 10.1093/humrep/13.12.3371
|View full text |Cite
|
Sign up to set email alerts
|

The performance of levonorgestrel rod and Norplant contraceptive implants: a 5 year randomized study

Abstract: A new contraceptive (LNG rod implants, Jadelle, Leiras Oy's registered trademark for rod implants) was prospectively evaluated in randomized 5 year comparison with Norplant (Population Council's registered trademark for contraceptive implants releasing levonorgestrel) capsule implants. The study involved 1198 women at seven centres. No pregnancies occurred in the first 4 years. At 5 years, the cumulative pregnancy rate was 1 per 100 users or less for each regimen. Annual discontinuation rates averaged 11-12 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 33 publications
7
51
1
6
Order By: Relevance
“…5,6 Study participants who continued to experience prolonged or irregular bleeding became increasingly dissatisfied over time. As with other studies, 5,7,8 bleeding problems were the most common reason for removal. Ten percent of participants stated that bleeding problems, either alone or with hormonal side effects, were the reason they sought removal of their implant.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…5,6 Study participants who continued to experience prolonged or irregular bleeding became increasingly dissatisfied over time. As with other studies, 5,7,8 bleeding problems were the most common reason for removal. Ten percent of participants stated that bleeding problems, either alone or with hormonal side effects, were the reason they sought removal of their implant.…”
Section: Discussionsupporting
confidence: 77%
“…5 At five years, 55% of women were still using the Jadelle® implant, giving a cumulative 5-year life table discontinuation rates for menstrual problems of 16.4/100. 7 More recent studies such as the Choice project had similar discontinuation rates to those of this study with 17% at 1 year for Implanon® users. 16 Total study discontinuation rates, made up of both known removals and loss to follow up rates, showed no difference between ethnicities and age.…”
Section: Discussionsupporting
confidence: 72%
“…4,23 However, studies in Asia showed significant weight gain in some clients warranting request for removal of the implant, while a study in Pakistan found significant increase in mean body weight of clients by the end of 2 years of usage. 23,28 There were a few non-menstrual side effects in Jadelle users in this study noted at 6months of usage, although the proportion of clients who had these side effects by the 12month of survey decreased, in agreement with similar studies elsewhere in the world. 4,25,26 Conversely, a different study found in addition more serious side effects like upper limb neuropathies, nervousness, visual disturbances, arthropathies, and non-clinical depression.…”
Section: Discussionsupporting
confidence: 89%
“…54 Single-rod etonogestrel (3-keto desogestrel) in EVA polymer implants give an initial release rate of about 60 micrograms/day, which maintains serum levels well above those needed to inhibit ovulation (90 pg/ml) for 3 years. 55 They are inserted using a disposable applicator.…”
Section: Subdermal Implantsmentioning
confidence: 99%